Simvastatin attenuates neutrophil recruitment in one-lung ventilation model in rats - Leite,Camila Ferreira (2013)
PURPOSE: To investigate the anti-inflammatory effects of simvastatin in rats undergoing one-lung ventilation (OLV) followed by lung re-expansion. METHODS: Male Wistar rats (n=30) were submitted to 1-h OLV followed by 1-h lung re-expansion. Treated group received simvastatin (40 mg/kg for 21 days) previous to OLV protocol. Control group received no treatment or surgical/ventilation interventions. Measurements of pulmonary myeloperoxidase (MPO) activity, pulmonary protein extravasation, and serum levels of cytokines and C-reactive protein (CRP) were performed. RESULTS: OLV significantly increased the MPO activity in the collapsed and continuously ventilated lungs (31% and 52% increase, respectively) compared with control (p<0.05). Treatment with simvastatin significantly reduced the MPO activity in the continuously ventilated lung but had no effect on lung edema after OLV. The serum IL-6 and CRP levels were markedly higher in OLV group, but simvastatin treatment failed to affect the production of these inflammatory markers. Serum levels of IL-1β, TNF-α and IL-10 remained below the detection limit in all groups. CONCLUSIONS: In an experimental one-lung ventilation model pre-operative treatment with simvastatin reduces remote neutrophil infiltration in the continuously ventilated lung. Our findings suggest that simvastatin may be of therapeutic value in OLV-induced pulmonary inflammation deserving clinical investigations.